SUCCESSFUL TWO PREGNANCIES IN ACHONDROPLASIC MOTHER, A CASE REPORT - Miskeen, Elhadi; Elsanousi, Mohamed; Sid Ahmed, Rihab; M. Elhassan, Elhassan; Omer Zeidan, Hussain; A/Rahman, Abuammmar; Ahmed Almustafa, Elsadig; Mirghani, Omer Ahmed (Gezira Journal of Health Sciences, 2009)
The word achondroplasia is derived from Greek and means "without cartilage formation," although individuals with achondroplasia do have cartilage. In genetics , dominance describes the effects of the different versions of a particular gene on the phenotype of an organism. Many animals (including humans) and plants have two copies of each gene in their genome, one inherited from each parent.